Introduction. From depictions of race to revitalizing a people: aspects of research on the Sámi in Finland and Norway - Nyyssönen, Jukka; Lehtola, Veli-Pekka (Northern Arctic Federal University, 2017)
In this special section of journal “Arctic and North” renowned and younger scholars from Finland and Norway take on the topic of research on the Sámi, from the era of “Lappology” to the era of “Sámi research”. The focus in the articles varies between research history, historiography and history of science. Thematically, the articles range from longer overviews of the historical evolution and transformation of “Lappology” in their national settings to more focused articles on individual scholars, as well as an article on Sámi historiography with a methodological approach. Two articles focus on the genesis of more culturally sensitive Sámi research.